Evaluación citogenética y de pérdida de la heterocigosidad de la región 22q11.2 en pacientes con el Síndrome de DiGeorge (2011)
ABSTRACT: To evaluate the usefulness of PCR for microsatellite markers (PCR-STR) in the 22q11.2 region of the genomic DNA in order to identify microdeletions in patients with the DiGeorge syndrome (DGS). Methodology: Clinical information was obtained from the medical charts of three DGS patients. Deletions in the chromosomic region 22q11.2 were investigated using FISH and PCR-STR. Results: We detected 22q11.2 deletions in two of the patients using FISH. Through PCR-STR, we identified the centromere-proximal 1.5 Mb deletion in patient n.º 1, the second most common defect in DGS. This deletion was of paternal origin. In order to better characterize the molecular defect in the other two patients included in this study, cromatographic analyses should be coupled to the PCR-STR. This would allow more accurate determination of the molecular weight of each parental allele. Also, more microsatellite markers in the 22q11.2 region should be analyzed to better define the deletion size. Conclusions: PCR-STR using the genomic DNA is a good alternative to identify deletions affecting microsatellites in the 22q11.2 region. In comparison to FISH, the PCR-STR is easy to carry out, less expensive and equally reliable in the detection of typical deletions. PCR-STR also allows to determine the parental origin and the deletion size, a valuable information to identify genes associated with the clinical manifestations of this syndrome.